FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA PUSKESMAS PANIKI BAWAH KECAMATAN MAPANGET - Princess Kambong; Olga Lieke Paruntu (POLTEKKES KEMENKES MANADO, 2013)
Infectious diseases are still a major disease in many developing countries, includingIndonesia. Infectious diseases in Indonesia that affects many infants are AcuteRespiratory Infection (ARI). In the Indonesian case acute respiratory tract infection (ARI )station is the first cause of infant deaths in each year . In addition ISPA also often be onthe list of 10 most diseases in hospitals . Factors that influence the occurrence of ARI ininfants include: nutritional status, age, breastfeeding, vitamin A supplementation irregular,incomplete immunization, air population, density of housing, socio-economic andeducational levels. Research purposes to determine what factors are associated with theincidence of ARI in the Puskesmas Paniki Bawah Mapanget District .This research uses a form of observational analytic study with descriptive statisticaltechniques. Data analysis was done by descriptive statistics and frequency distributiontables and narrated as well as statistical analysis. To examine the relationship betweenvariables Chi - Square test and Fisher 's Exact test alternative to using the softwareprogram for Social Statistics Programme Sciense (SPSS). Results of this study showedthat exclusive breastfeeding factors have a relationship with the incidence of respiratorydisease in young children, it is because the immune milk given by not properly fulfilled soeasily toddlers up to disease. For other factors that are not observed a significantrelationship between the independent variables and the dependent variable. Given it isexpected that the government and local health officials to improve the coverage ofexclusive breastfeeding to provide information about the benefits of exclusivebreastfeeding for the child so that the mother can understand and provide exclusivebreast milk for her child.